PENAMBAHAN JUS DAUN SIRIH (Piper betle Linn) PADA RANSUM AYAM PETELUR TERHADAP PENURUNAN KOLESTEROL TELUR - Ahmad Khoirul; Edya Moelia Lubis (Universitas Islam Balitar, 2017)
The purpose of this study was to determine the volume increase in betel leaf juice ration of laying hens egg cholesterol reduction. This study uses layer laying hens period of 250 heads aged 50 weeks from Isa Brown strain. The method used is an experimental method that consists of five treatments and five repetitions, and each repeat consists of 10 of chicken with P0 treatment (basal feed), P1 (basal feed + 5 ml juice of betel leaves), P2 (basal feed + 7.5 ml juice of betel leaves), P3 (basal feed + 10 ml juice of betel leaves), and P4 (basal feed + 12.5 ml juice of betel leaves). Data using analysis with Analysis of Varience (ANOVA) if significant level using by Duncan test. The results showed that addition of betel leaf juice in the diet of laying chickens highly significant effect (P <0.01) to decrease cholesterol eggs with the best volume is 12.5 ml (P4) as shown by the higher volume of betel leaf juice added to feed laying hens is the higher the tendency of decrease cholesterol eggs. Recommended the addition of juice of betel leaves effectively using 12.5 ml in volume decrease cholesterol eggs.Keywords: juice of betel leaf, laying hens and egg cholesterol.